Enhancing Researchers' Performance by Building Commitment to Organizational Results. Issue 2 (3rd March 2020) - Loyarte-López, Edurne; García-Olaizola, Igor; Posada, Jorge; Azúa, Iñaki; Flórez-Esnal, Julián
Abstract : Overview: Performance measurement systems are a fundamental concern for R&D managers and executives. The main challenge is ensuring that R&D managers can match organizational key performance indicators with researchers' interests. This article details a new approach to measuring the fuzzy parameter of researchers' performance. It presents a case study on the implementation of a rating system in a research technology organization and reports the results the system achieved, including researcher satisfaction. We describe which researcher skills were selected for rating, the evaluation criteria developed, and the data collection system that supported the rating process. The rating system was developed to be objective and acceptable to researchers, and to support achievement of desired corporate results. We present lessons learned from implementation over four years.